1997
DOI: 10.1097/00005392-199701000-00059
|View full text |Cite
|
Sign up to set email alerts
|

Systematic 5 Region Prostate Biopsy is Superior to Sextant Method for Diagnosing Carcinoma of the Prostate

Abstract: We introduce the 5 region technique of prostate biopsy as a means of significantly increasing the diagnostic yield of prostate biopsy in finding carcinoma of the prostate. We have found this technique to be safe, efficacious and superior to the sextant method of biopsy in identifying prostate cancer at an early but significant stage. The greatest use of the 5 region biopsy technique is in patients who have prostate specific antigen levels between 4 and 10 ng./ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
193
5
12

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(216 citation statements)
references
References 9 publications
6
193
5
12
Order By: Relevance
“…For the 493 men who underwent biopsy, this equates to a 6% increase in the rate of cancer detection from 27% (sextant only, 133/493) to 33% (extended biopsies, 164/493). This ®nding is in general agreement with other published extended biopsy protocols [7,21,22]. Although the present sampling technique may have differed from those in other reports, it is clear that prostate cancer detection can be signi®cantly improved by taking more biopsies (within reason) and sampling regions of the prostate not incorporated in the routine sextant protocol.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For the 493 men who underwent biopsy, this equates to a 6% increase in the rate of cancer detection from 27% (sextant only, 133/493) to 33% (extended biopsies, 164/493). This ®nding is in general agreement with other published extended biopsy protocols [7,21,22]. Although the present sampling technique may have differed from those in other reports, it is clear that prostate cancer detection can be signi®cantly improved by taking more biopsies (within reason) and sampling regions of the prostate not incorporated in the routine sextant protocol.…”
Section: Discussionsupporting
confidence: 90%
“…Initially we were surprised at the relatively few additional tumours detected by lateral PZ biopsies, as many groups have reported a signi®cant improvement in cancer detection rates with this technique [7,8,21]. However, the present detection rate of an additional 6% of tumours con®ned exclusively to the lateral PZ compares favourably with Ravery et al [23], who noted a 6.6% overall improvement in prostate cancer detection with the addition of 4 ±6 lateral PZ biopsies, depending on prostate volume.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…6 Several groups have since demonstrated that complementing the sextant format with further biopsies will optimize cancer detection rates without increasing morbidity. [7][8][9][10] Regardless of the increased number of biopsies that are obtained, detection rates are still typically only 30-44%. 7,9 In the remaining patients the question is whether the elevated PSA is due to other causes vs cancer that went undetected.…”
Section: Introductionmentioning
confidence: 99%